Use of DNA barcoding to distinguish the malaria vector Anopheles neivai in Colombia - López-Rubio, Andrés; Suaza-Vasco, Juan; Marcet, Paula L; Ruíz-Molina, Natalia; Cáceres, Lorenzo; Porter, Charles; Uribe, Sandra (Zootaxa, 2016)
A reference 535 bp barcode sequence from a fragment of the mitochondrial gene cytochrome oxidase I (COI), acquired from specimens of An. neivai Howard, Dyar & Knab, 1913 from its type locality in Panama, was used as a tool for distinguishing this species from others in the subgenus Kerteszia. Comparisons with corresponding regions of COI between An. neivai and other species in the subgenus (An. bellator Dyar & Knab 1906, An. homunculus Komp 1937, An cruzii Dyar & Knab, 1908 and An. laneanus Corrêa & Cerqueira, 1944) produced K2P genetic distances of 8.3–12.6%, values well above those associated with intraspecific variation. In contrast, genetic distances among 55 specimens from five municipalities in the Colombian Pacific coastal state of Chocó were all within the range of 0–2.5%, with an optimized barcode threshold of 1.3%, the limit for unambiguous differentiation of An. neivai. Among specimens from the Chocó region, 18 haplotypes were detected, two of which were widely distributed over the municipalities sampled. The barcode sequence permits discrimination of An. neivai from sympatric species and indicates genetic variability within the species; aspects key to malaria surveillance and control as well as defining geographic distribution and dispersion patterns.